2016
DOI: 10.3233/wor-152238
|View full text |Cite
|
Sign up to set email alerts
|

Work-related stress among correctional officers: A qualitative study

Abstract: Abstract.7 BACKGROUND: Correctional officers (COs) are exposed to various factors likely to jeopardize their health and safety. Even if numerous studies have been focused on work-related stress among COs, few studies have been carried out in Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 43 publications
8
36
1
Order By: Relevance
“…International research, with the aim of studying the causes and effects of burnout in prison officers, has grown strongly, particularly in the last decade. However, as stated by Viotti (2016), there are still very few studies in the Italian context. Research carried out by Petitta et al (2009) has shown that a sense of self-efficacy is a significant predictor of burnout.…”
Section: Burnout In the Context Of The Correctional Officermentioning
confidence: 99%
See 2 more Smart Citations
“…International research, with the aim of studying the causes and effects of burnout in prison officers, has grown strongly, particularly in the last decade. However, as stated by Viotti (2016), there are still very few studies in the Italian context. Research carried out by Petitta et al (2009) has shown that a sense of self-efficacy is a significant predictor of burnout.…”
Section: Burnout In the Context Of The Correctional Officermentioning
confidence: 99%
“…Research by Farnese et al (2017) has revealed how the presence of a mentor and socialization are crucial protective factors for correctional officers just assuming the role. Last, Viotti (2016) highlighted how the relationship with inmates represents a stressful factor that negatively affects the physical, cognitive, and, above all, emotional well-being of correctional officers. What’s more, correctional officer guilt and the perception of impotence due to the impossibility of helping inmates are seen as another source of stress.…”
Section: Burnout In the Context Of The Correctional Officermentioning
confidence: 99%
See 1 more Smart Citation
“…This research also revealed that the PCO's perceived risk of HCV exposure contributed to their anxiety. Finney et al (2013) and Viotti (2016) found when examining prison officers' stressors that this staff group experience more anxiety than other workers and that health risk fears were an important contributory factor. Prison nurses have a crucial role in providing ongoing support to prison staff mitigate their worries and ensure that any potential exposure to a BBV from a needles-stick injury or while de-escalating a fight is dealt with promptly, accurately and sensitively.…”
Section: Relevance To Clinical Practicementioning
confidence: 97%
“…Municipal police officers share a variety of stressinducing factors with active police officers [13]. Such factors include shift working, long working hours, frequent conflicts and unpredictability at work [14,15].…”
Section: Introductionmentioning
confidence: 99%